Randomized Split-Mouth Study on Postoperative Effects of Palmitoylethanolamide for Impacted Lower Third Molar Surgery. (6th April 2011) - Bacci, Christian; Cassetta, Giulia; Emanuele, Bruno; Berengo, Mario
Abstract : The aim of this study was to assess the efficacy of Normast 300 mg in reducing swelling and pain after the surgical extraction of impacted lower third molars. Materials and Methods . A randomized, split-mouth, single-blind study was conducted on 30 patients between 18 and 30 years of age requiring lower third molar extraction. Patients underwent bilateral extractions in a randomized sequence, one extraction being performed under Normast treatment. The Normast treatment involved 2 tablets a day for 15 days. The parameters assessed at each procedure were trismus, swelling, pain, NSAID consumption, postoperative complications, drug tolerability, and safety. The results obtained were processed using repeated measures analysis of variance. Results . Perceived postoperative pain was reportedly significantly milder on Normast treatment than control. The trend of the means differed over time( P < .0001 ) and between the two extraction groups( P < .0221 ) . On the other hand, for edema and trismus, the trend differed over time for both groups but did not differ between the two groups. Discussion . Our analyses indicate that patients experienced significantly less postoperative pain when they were treated with Normast. Conclusions . Administering Normast improves the postoperative course—in terms of pain—after lower third molar extraction.